La prescripción extintiva durante el desarrollo del procedimiento de ejecución coactiva de las multas impuestas por el indecopi - Rubio Medina, Martín León (2016)
This thesis contains a legal research on "the statute of limitations DURING THE DEVELOPMENT OF PROCEDURE FOR COMPLETION COERCIVE OF FINES IMPOSED BY INDECOPI" motivated considering that there is a regulatory gap and absence of specific doctrine on the subject in concrete, which it has generated me great concern considering that the research topic magazine of great importance because the absence of legal regulation or the establishment of a doctrinaire approach does not prevent people affected by the imposition of fines by the INDECOPI, there currently the only way to pay them, affecting the constitutional right of defense of people in care that would restrict their right to question them on the way to execution, with legal figures such as the "statute of limitations" obviously from the point of view of the defense as a lawyer, guarding the rights and interests of the sponsored. So that the present investigation seeks to give solution in a tangle of diverse and complex legal relations, one that has not been provided and regulated by the legal rules in specific, which means, in response to legislation and other regulations legal are imperfect, but not justified; that is why this research is intended to provide a legal solution to the problem; being so, step describe the body of this research: In the first part of the thesis the methodological framework and research plan made both by the following occur: motivation and research foundations; their background, if exists; the problematic reality; the justification of research; the problem and the respective hypothesis is formulated; the variables and objectives (general and specific) are established. In the second part of the thesis the theoretical framework, it is composed of chapters, the same that will develop the following occurs: the mechanisms of interpretation and legal integration, subsidiarity; general administrative procedure in Peru (classification, trilateral procedure, disciplinary procedure, principles, sources, etc.); the administrative act and its enforceability (principles, validity requirements, etc.); the loss of enforceability of the administrative act; the statute of limitations and expiration; the statute of limitations in civil law and other branches of law; the statute of limitations governed by special rules related to the role of INDECOPI; Coercive execution and the statute of limitations of the action; comment and developing the case. In the third part of the thesis the results, discussion thereof, the conclusions which have been reached with research and recommendations of case is presented. In the final part of the thesis reference to the literature it is made and the corresponding annexes attached. Thus, this research has sought where possible to observe the structure and conditions must contain a scientific report, constitute, indeed, a challenge I have undertaken since the beginning of the investigation; and aware of the comments on the development of research can be formulated, I submit to them, committing to overcome in the future